Analysis and Optimization of Drying of Green Bricks in a Tunnel Dryer - MANÇUHAN, EBRU (TAYLOR & FRANCIS INC, 2009)
One way to avoid the risk of condensation in a tunnel dryer for drying of green bricks is to use higher air flow rates. However, higher air flow rates accelerate the drying rate and thus cause damages. It is necessary to determine the optimal values of the hot and outdoor air mass flow rates and optimum stack temperature to avoid the condensation. Four different temperatures, (-5, 10, 20, and 30C) and three different relative humidities (40, 60, and 80%) for the outdoor air were selected. Optimal operation parameters and the required stack temperature to avoid condensation for different cases were computed.
Keywords: Drying air; Green bricks; Optimization; Tunnel dryer; MODEL